Europejczyk w Kartoflanii. O powrotach do "małej ojczyzny" w powieściach Mariana Pankowskiego - Fiszbak, Zbigniew (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The theme of the article is the return to the motherland in prose by Marian Pankowski - a Polish writer who lives in Belgium. In series of novels the author creates a literary character who, in fact, has a lot in common with hismelf. When the man is visiting his motherland, a confrontation takes place: a professor of a western university, an educated European writer, a rationalist and humanist versus his homeland - Kartoflania, that is provincial in respect of civilization and culture. The collision of the different mental worlds, brings to the light of day absurd and adulteration of the family, but simultaneously helps the literary character to restore his emotionally unstable connection with his family land. The main hero of novel tries to compensate his European identity for Polish origin.